2014
DOI: 10.4236/ojmc.2014.41001
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of N-Hydroxyethyl-4-aza-2,3-didehydropodophyllotoxin Derivatives upon Colorectal Adenocarcinoma Cells

Abstract: Etoposide is a chemotherapy drug derived from the natural lignin podophyllotoxin. Our novel generated Aza-podophyllotoxin compounds (AZP 8a & AZP 9a) are analogues of podophyllotoxin and were previously screened for anti-cancer activity through the NCI 60 cell line screening panel showing activity on various cell types including colon cancer. This study expands the toxicological screening by studying apoptosis and various hallmark events as part of the mechanism of action of these compounds on colon cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…For example, the presence of dead cells by apoptosis and necrosis may be due to the compounds found in the extract, such as podophyllotoxin. This compound registered a greater abundance in the GC-MS. We found that the extract promotes the externalization of phosphatidylserine and a loss of mitochondrial membrane potential, these events are characteristic during programmed cell death (PCD) (Mehta and Shaha, 2004;Sen et al, 2007), and these findings are consistent with those reported by Velez et al (2014), who reported that podophyllotoxin and its analogues have the ability to generate apoptosis in COLO-205 cells to promote the externalization of phosphatidylserine between 20 % and 50 %. This generates permeability of the mitochondrial membrane.…”
Section: Discussionsupporting
confidence: 81%
“…For example, the presence of dead cells by apoptosis and necrosis may be due to the compounds found in the extract, such as podophyllotoxin. This compound registered a greater abundance in the GC-MS. We found that the extract promotes the externalization of phosphatidylserine and a loss of mitochondrial membrane potential, these events are characteristic during programmed cell death (PCD) (Mehta and Shaha, 2004;Sen et al, 2007), and these findings are consistent with those reported by Velez et al (2014), who reported that podophyllotoxin and its analogues have the ability to generate apoptosis in COLO-205 cells to promote the externalization of phosphatidylserine between 20 % and 50 %. This generates permeability of the mitochondrial membrane.…”
Section: Discussionsupporting
confidence: 81%
“…Some previous studies proposed that hydroxyethyl derivatives exhibited stronger anticancer activity. 59,60 Further, the results of histological examination for the tumor micrograph of EAC + Ch and EAC + Ch + R mice groups compared to EAC mice reveals noticeable amelioration in cell architecture of the muscle bundle in addition to certain improvement in the state of tumor cell infiltration, penetration and area of necrosis, and enhancing tumor cells apoptosis (Figure 7). The results give the impression that Ch plays an efficient role in the inhibition of the TNF-α and IFN-γ activation event.…”
Section: Discussionmentioning
confidence: 98%
“…With this aim, a new class of potential antitumor agents, azapodophyllotoxins (AZPs), that are nitrogen derivatives of podophyllotoxin have been designed and synthesized [3–7] . Interestingly, these AZPs were highly effective for wide spectrum of cancers as studied so far [8–11] …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Interestingly, these AZPs were highly effective for wide spectrum of cancers as studied so far. [8][9][10][11] In the present study, a fascinating AZP derivative, 5-(2-Hydroxyethyl)-9-(3,4,5-trimethoxyphenyl)-6,9-dihydro- [1,3]dioxolo [4,5-g]furo [3,4-b] quinolin-8(5H)-one (HTDQ), (Figure 1) has been investigated that exhibits excellent anticancer activities with GI50 values of less than 1 μM for most of the cancer cell lines. [12] The remarkable properties of these AZPs have beckoned exploration of its mechanism of action.…”
Section: Introductionmentioning
confidence: 99%